2012
DOI: 10.1016/j.jml.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-dimensional dependencies in implicit phonotactic learning

Abstract: Is phonological learning subject to the same inductive biases as learning in other domains? Previous studies of non-linguistic learning found that intradimensional dependencies (between two instances of the same feature) were learned more easily than inter-dimensional ones. This study compares implicit learning of intra-and inter-dimensional phonotactic dependencies. A series of six unsupervised implicit-learning experiments shows that a pattern based on agreement between two instances of the same feature is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 90 publications
(95 reference statements)
2
71
0
Order By: Relevance
“…The size of the interaction was small, and detectable only among identical vowels. This offers the potential for a perceptual explanation for distance effects, but such an explanation is not the only plausible account; for example, it may very well be the case that biases in learning systematically disadvantage patterns that require associations across increasing distances (see Moreton, 2012;Moreton & Pater, 2012 for more on structural biases in learning).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the interaction was small, and detectable only among identical vowels. This offers the potential for a perceptual explanation for distance effects, but such an explanation is not the only plausible account; for example, it may very well be the case that biases in learning systematically disadvantage patterns that require associations across increasing distances (see Moreton, 2012;Moreton & Pater, 2012 for more on structural biases in learning).…”
Section: Discussionmentioning
confidence: 99%
“…In both phases, the words were presented in isolation-i.e., not in a continuous stream. Participants were told that the exposure phase would be followed by a test phase during which they will be required to decide if new words sounded like they could belong to the language they were listening to (for a similar task, see Moreton, 2008Moreton, , 2012Reeder et al, 2013). During the test phase, the instructions for the task were repeated after every test word.…”
Section: Methodsmentioning
confidence: 99%
“…The simplest type of such a generalization is sound identity (repetition). A large range of studies have shown that such generalizations can be acquired in artificial language studies (Gervain, 2014;Marcus et al, 1999;Moreton, 2012). In natural languages, generalizations that have to do with segment repetition or bans on repetition have been documented in Yucatec Mayan, Hebrew, Peruvian Aymara, and other languages (Berent et al, 2002;Gallagher, 2013).…”
Section: Experiments 2a: a Probabilistic Abstract Generalizationmentioning
confidence: 98%
“…In pattern 5, the two features relevant to the pattern are on the same consonant, and in pattern 6, they are on two separate consonants. Moreton (2012) claims that there is an advan- C1+voi and C1+cor C1-voi and C1-cor 6…”
Section: Patternsmentioning
confidence: 99%